Standardized in-vitro evaluation of CAR-T cells using acellular artificial target particles - Harari-Steinfeld, Rona; Abhinav Ayyadevara, V. S. S.; Cuevas, Lizette; Marincola, Francesco; Roh, Kyung-Ho (Frontiers in Immunology, 2022)
The horizon of immunotherapy using CAR-T cells is continuously extending to treat solid tumors beyond the success in the treatment of liquid tumors. Precise in-vitro evaluations of CAR-T cells for their phenotypes, quantity and quality of activation in various tumor microenvironments including different antigen densities, and the resulting effector functions are critical for the successful development of CAR-T therapies and safe translation to clinics. Unfortunately, the development of methods and tools to accommodate these needs have been lagging behind. Here, we developed a novel biomaterial platform, acellular artificial target particles (aaTPs) against CAR-T cells, using magnetic microbeads that are already widely employed in the manufacturing of T cell products. By devising a simple and standardized procedure, we precisely controlled the antigen surface densities presented on the aaTPs for a wide range. By co-incubation of aaTPs with CAR-T cells followed by flow cytometry and cytokine assays, we quantitatively determined the antigen-specific and dose-dependent activation of anti-HER2 CAR-T cells. We also demonstrated that the aaTP can serve as a clean target cell in in-vitro assays to prove the proposed mechanism of action of a next-generation CAR-T product. Overall, the simple, inexpensive, modular and precisely controllable synthetic nature of aaTPs enables the development of clean and standardized in-vitro assays for CAR-T cells, which provides critical advantages over the conventional assays using target cell lines. The design of aaTPs can be extended to include other tumor antigens and relevant surface molecules of physiological target cells. Thus, the aaTP platform has great potential as a standardized tool for the development and evaluation of both conventional and new CAR-T products in the context of approval from regulatory agencies and clinical translation.